2017
DOI: 10.3847/2041-8213/835/2/l37
|View full text |Cite
|
Sign up to set email alerts
|

Solar Ellerman Bombs in 1D Radiative Hydrodynamics

Abstract: Recent observations from the Interface Region Imaging Spectrograph appear to show impulsive brightenings in high temperature lines, which when combined with simultaneous ground-based observations in Hα, appear cospatial to Ellerman Bombs (EBs). We use the RADYN one-dimensional radiative transfer code in an attempt to try and reproduce the observed line profiles and simulate the atmospheric conditions of these events. Combined with the MULTI/RH line synthesis codes, we compute the Hα, Ca II 8542 Å, and Mg II h … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 38 publications
3
33
0
Order By: Relevance
“…Reid et al (2017) first calculated the line profiles of EBs using a thermal model, with results similar to observations. However, as EBs are believed to be caused by magnetic reconnection, the non-thermal effects by electrons, which they did not take into consideration, might be important.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Reid et al (2017) first calculated the line profiles of EBs using a thermal model, with results similar to observations. However, as EBs are believed to be caused by magnetic reconnection, the non-thermal effects by electrons, which they did not take into consideration, might be important.…”
Section: Introductionmentioning
confidence: 88%
“…The Mg II k line profiles are computed using the RH code (Uitenbroek 2001;Pereira & Uitenbroek 2015), and the integrated intensity of the Si IV 1403 Å line over wavelength is calculated using the CHIANTI atomic database (Del Zanna et al 2015). One can see that, similar to Reid et al (2017), the outer wings of the Mg II k line are enhanced, while there is very little influence on the k 2 peaks. The light curve of the Si IV integrated intensity shows very little fluctuation, which is atypical in UV bursts.…”
Section: Comparison Between Simulations and Observationsmentioning
confidence: 99%
“…Due to the contribution function of Ca II 8542Å encompassing a broad range of heights along the photosphere and chromosphere (Cauzzi et al 2008;Reid et al 2017), some stratification with height would also be necessary in order to fully utilize the observations. The input observations were optimized in order to accumulate a sufficient signal in Stokes-Q, -U, and -V. The area within the red box of Figure 1 was used for the inversions and was spatially binned 2 × 2.…”
Section: Nicole Inversionsmentioning
confidence: 99%
“…Bi-directional flows have also been reported in EBs, with the upflows showing a higher velocity than the downflows at EB locations, with values much lower than that of micro-flares (±5 km s −1 ; Isobe et al 2007;Matsumoto et al 2008;Archontis & Hood 2009;Reid et al 2017).…”
mentioning
confidence: 99%
“…More recently, it has also been found that some EBs correspond to small-scale compact brightenings in the 1700 Å images taken by the Atmospheric Imaging Assembly (AIA, Lemen et al 2012) onboard the solar dynamics observatory (SDO) (Vissers et al 2013;Tian et al 2016;Zhao et al 2017;Toriumi et al 2017 Peter et al 2014;Vissers et al 2015;Cho et al 2015;Tian et al 2016;Grubecka et al 2016). However, it is still under debate whether such intense heating is directly caused by the EBs or not (e.g., Lei et al 2016;Reid et al 2017;Berlicki and Heinzel 2014;Fang et al 2017;Hong et al 2017;Danilovic 2017;Hansteen et al 2017). …”
Section: Introductionmentioning
confidence: 99%